Testing Antioxidant Activity of Pineapple (Ananas Comossus Merr.) Rinds Using UV-Vis Spectrophotometry Method - Syahputra, Andi; Halimatussakdiah, Halimatussakdiah; Amna, Ulil (Universitas Syiah Kuala, 2024)
Pineapple (Ananas comossus Merr.) is one of the plants that is widespread in tropical and subtropical areas. This plant content vitamin C and antioxidant activity. This study was conducted to identify the class of secondary metabolite compounds and determine the antioxidant activity of pineapple fruit peel. Antioxidant activity testing on pineapple fruit peel was conducted using UV-Vis spectophotometric method with wavelength of 514 nm. The identification of secondary metabolite compounds showed that the methanol extract of pineapple fruit peel contains alkaloid, flavonoid, phenol, tannin and saponin compounds. Antioxidant activity of methanol extract of pineapple fruit peel carried out by DPPH (1,1-diphenyl-2-picryldhydrazyl) method shows IC50 value of 92.87 ppm with strong category, while vitamin C as a comparison has IC50 value of 9.31 ppm with very strong category. This is due to the pineapple fruit peel containing high levels of vitamin C. In addition, pineapple fruit peel contains secondary metabolites, especially flavonoids, phenols and tannins which are a class of polyphenolic compounds.